FORUM KEMITRAAN POLISI MASYARAKAT (FKPM) DALAM PENYELESAIAN TINDAK PIDANA RINGAN (Studi tentang Hubungan Polisi dan Masyarakat di Kelurahan Perumnas Way Kandis, Kota Bandar Lampung) - Fajri, Danial Nuril; Syah, Pairul (SOCIOLOGIE, 2013)
The Public and Police Partnership Forum (or FKPM) is a non government organization aimed to settle venial crime case often occurring in the society and it function to support and help police tasks in maintaining security, orderliness and peace in the society. The objective of this research was to find out the cooperation relationship between police and public to settle venial crime cases in forms of mediations. This was a qualitative research. Data were collected with interviews, informant determinations and documentation study. Data were analyzed with data reduction, data presentation, and drawing conclusion. The results showed that the Public and Police Partnership Forum (or FKPM) in Way Kandis Residence Village was very effective in settling venial crime cases. It was proven that each venial crime case could be resolved without proceeding to legal suit by means of mediations. The success of Public and Police Partnership Forum (FKPM) in conducting its functions was closely related to good cooperation between public and police in frequent socialization activities about task and function of Public and Police Partnership (FKPM). Public tasks in this institution were becoming an information centre, criticism and suggesting constructive recommendations to create good partnerships in maintaining security, orderliness and peace in the society.Keywords: FKPM, institution, mediation